Study of Structuralism, Post-Structuralism and Network Actors and Their Relevance to Islamic Education : Kajian Teori Strukturalisme, Post- Strukturalisme dan Aktor Jaringan serta Relevansinya dengan Pendidikan Islam - Isa Anshori (Universitas Muhammadiyah Sidoarjo, 2020)
Important developments related to the recent history of social theories, including the soci- ology of education, are revolutions that take place in linguistics and lead to the search for structures that underlie language. Structuralism, as the name of the revolution, later influenced various fields of social science, such as the anthropology of Levi-Strauss and Marxian theory, Structural Marxism. The most important post-structuralist is Michel Fou- cault. The latest theory derived from semiotics, structuralism, and post-structuralism is the actor-network theory, seeing social processes and human actors as entities whose characteristics are born from circulation through a network of relations. In Islamic educa- tion, the study of the structure of language becomes very important, because language is a communication tool of the education and learning process, besides that it is also a publication for the development of education to the wider community.